Electricity energy outlook in Malaysia - Tan C.S.; Maragatham K.; Leong Y.P. (Institute of Physics Publishing, 2023)
Population and income growth are the key drivers behind the growing demand for energy. Demand for electricity in Malaysia is always growing in tandem with its Gross Domestic Product (GDP) growth. The growth for electricity in Malaysia forecasted by Economic Planning Unit (EPU) has shown an increase of 3.52% in 2012 compared to 3.48% in 2011. This growth has been driven by strong demand growth from commercial and domestic sectors. The share of electricity consumption to total energy consumption has increased from 17.4% in 2007 to 21.7% in 2012. The total electricity production was reported at 122.12TWh in 2012, where gas is still the major fuel source contributing to 52.7% of the total generation fuel mix of electricity followed by Coal, 38.9%, hydro, 7.3%, oil, 1% and others, 0.2%. This paper aims to discuss the energy outlook particularly the electricity production and ways toward greener environment in electricity production in Malaysia Published under licence by IOP Publishing Ltd.